2015
DOI: 10.1093/rheumatology/kev262
|View full text |Cite|
|
Sign up to set email alerts
|

Increased risk of cardiovascular disease in giant cell arteritis: a general population–based study

Abstract: These findings provide general population-based evidence that GCA patients are at a substantially increased risk of cardiovascular disease. Increased monitoring for this potentially fatal outcome and its modifiable risk factors is warranted for GCA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 39 publications
5
39
0
Order By: Relevance
“…These results are similar to those of previously reported increased rates of stroke, myocardial infarction, and peripheral vascular disease among patients with GCA in a large UKbased population (13). This study showed quite similar results to those in the recently published data from Amiri et al on the rate of ischemic heart diseases and CVA among patients with GCA (14). However, the rate ratios compared with reference population were higher in the Canadian study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are similar to those of previously reported increased rates of stroke, myocardial infarction, and peripheral vascular disease among patients with GCA in a large UKbased population (13). This study showed quite similar results to those in the recently published data from Amiri et al on the rate of ischemic heart diseases and CVA among patients with GCA (14). However, the rate ratios compared with reference population were higher in the Canadian study.…”
Section: Discussionsupporting
confidence: 91%
“…Udayakumar et al demonstrated no overall increased in the rate of acute coronary syndrome among patients with GCA (15). The association between GCA and coronary artery disease is unclear with varied findings among several population-based studies (13)(14)(15). Differences in case ascertainment of cases of GCA (study criteria vs. biopsy-proven GCA) may explain such variations.…”
Section: Discussionmentioning
confidence: 99%
“…For the incidence of GCA-related stroke, the models assume that 2.64% of cases of GCA result in a stroke, as per Amiri et al, 90 and further assume that strokes arise after presentation to the patient's GP. It is also assumed that stroke occurring as a result of GCA has the same severity and likelihood of fatality as stroke unrelated to GCA.…”
Section: Strokementioning
confidence: 99%
“…20 NO. 90 and quality of life (e.g. through reduced incidence of blindness or reduced incidence of fractures).…”
mentioning
confidence: 99%
“…Based on retrospective studies, GCA is associated with an increased prevalence of traditional cardiovascular (CV) risk factors and CV events, including myocardial infarction and stroke 1,2,3,4,5 . However, studies regarding management of CV disease (CVD) in GCA are lacking.…”
Section: To the Editormentioning
confidence: 99%